2014
DOI: 10.1088/2041-8205/787/1/l10
|View full text |Cite
|
Sign up to set email alerts
|

DISCOVERY OF FINELY STRUCTURED DYNAMIC SOLAR CORONA OBSERVED IN THE Hi-C TELESCOPE

Abstract: In the Summer of 2012, the High-resolution Coronal Imager (Hi-C) flew on board a NASA sounding rocket and collected the highest spatial resolution images ever obtained of the solar corona. One of the goals of the Hi-C flight was to characterize the substructure of the solar corona. We therefore examine how the intensity scales from AIA resolution to Hi-C resolution. For each low-resolution pixel, we calculate the standard deviation in the contributing high-resolution pixel intensities and compare that to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…Most interestingly, Brooks et al (2013) show an occurrence distribution of 91 hand-picked loops observed with Hi-C with a minimum Gaussian width of σ w = 90 km (FWHM=212 km) and an average Gaussian width of σ w = 272 km (FWHM=640 km), which is fully consistent with our result of a peak width (FWHM) of w p ≈ 550 km based on three orders of magnitude larger statistics. Winebarger et al (2014) conducted a statistical analysis of the noise characteristics of a Hi-C image and concluded that 70% of the pixels in each Hi-C image do not show evidence for significant substructures, which confirms the scarcity of thinner loop strands than observed so far (see also Fig. 11b, where no structures except data noise is visible).…”
Section: Comparison With Previous Loop Width Measurementssupporting
confidence: 61%
“…Most interestingly, Brooks et al (2013) show an occurrence distribution of 91 hand-picked loops observed with Hi-C with a minimum Gaussian width of σ w = 90 km (FWHM=212 km) and an average Gaussian width of σ w = 272 km (FWHM=640 km), which is fully consistent with our result of a peak width (FWHM) of w p ≈ 550 km based on three orders of magnitude larger statistics. Winebarger et al (2014) conducted a statistical analysis of the noise characteristics of a Hi-C image and concluded that 70% of the pixels in each Hi-C image do not show evidence for significant substructures, which confirms the scarcity of thinner loop strands than observed so far (see also Fig. 11b, where no structures except data noise is visible).…”
Section: Comparison With Previous Loop Width Measurementssupporting
confidence: 61%
“…In the context of coronal imaging, HiC has an unprecedented plate scale of 0.1 pixel −1 , which corresponds to 73 km pixel −1 on the Sun. The image resolution estimated by Winebarger et al (2014) is 0.3 to 0.4 . The 4k×4k full-frame images were recorded with an exposure time of 2 s at a cadence of 5.5 s. The unprecedented spatial and temporal resolution achieved by the Hi-C allows us to carry out the detailed analysis of the small-scale arcsec-size structures discussed in the introduction that were not resolved by previous instruments.…”
Section: Observationsmentioning
confidence: 99%
“…Current instrumentation indicates that the chromosphere and corona is finely structured, with typical transverse scales of ∼ 400 km (De Pontieu et al 2007a, Morton et al 2012, Brooks et al 2013, Morton & McLaughlin 2013, 2014, Winebarger et al 2014. The fine-scale structure is seen to support MHD waves, and theoretical considerations demonstrate that these (likely) over dense magnetic flux tubes act as waveguides, funnelling the wave energy through the solar atmosphere.…”
Section: Introductionmentioning
confidence: 99%